Comparison of reliability, construct validity and responsiveness of the IPAQ‐SF and PASE in adults with osteoarthritis. (8th March 2021) - Smith, R.D.; McHugh, G.A.; Quicke, J.G.; Dziedzic, K.S.; Healey, E.L.
Abstract: Background: This study assessed the measurement properties of two commonly used self‐report physical activity (PA) measures: the International Physical Activity Questionnaire—Short Form (IPAQ‐SF) and the Physical Activity Scale for the elderly (PASE) in adults with osteoarthritis. Methods: Secondary analysis of the MOSAICS cluster randomised controlled trial baseline and 3‐month follow‐up questionnaires, total scores and subdomains of the IPAQ‐SF and PASE were compared. Intra‐class correlations (ICC) were used to assess test–retest reliability, measurement error was assessed using standard error of measurement (SEM), smallest detectable change (SDC) and 95% limits of agreement (LoA). Responsiveness was assessed using effect size (ES), standard responsive measurement (SRM) and response ratio (RR). Results: There was moderate correlation ( r  = 0.56) between the total IPAQ‐SF scores (score ranges 0–16, 398) and the total PASE scores (score ranges 0–400). Subdomain correlations were also moderate (ranges 0.39–0.57). The PASE showed greater reliability compared to the IPAQ‐SF (ICC = 0.68; 0.61–0.74 95% CI and ICC = 0.64; 0.55–0.72, respectively). Measurement errors in both measures were large: PASE SEM = 46.7, SDC = 129.6 and 95% LoA ranges = −117 to 136, the IPAQ‐SF SEM = 3532.2 METS −1 min−1 week, SDC = 9790.8 and 95% LoA ranges = −5222 to 5597. Responsiveness was poor: ES −0.14 and −0.16, SRM −0.21 and −0.21, and RR 0.12 and 0.09 for the IPAQ‐SF and PASE, respectively. Discussion: The IPAQ‐SF and PASE appear limited in reliability, measurement error and responsiveness. Researchers and clinicians should be aware of these limitations, particularly when comparing different levels of PA and monitoring PA levels changes over time in those with osteoarthritis.